Kinetic isotope effects and reaction intermediates in the decomposition of methyl on flat and stepped platinum (1 1 1) surfaces - Papp, Christian; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2007)
We investigated the thermal evolution of methyl on Pt(1 1 1), Pt(3 2 2) and Pt(3 5 5) by in situ X-ray photoelectron spectroscopy. The dehydrogenation to methylidyne shows a pronounced kinetic isotope effect, with the characteristic temperature higher by 16 K for CD than for CH. The resulting difference in activation energies, 48 meV, agrees well with the difference in the zero point energies of the C-H and C-D stretching vibrations. For the stepped surfaces an enhanced reactivity is found. While dehydrogenation of methyl on Pt(3 2 2) at step and terrace sites occurs at the same temperature, for Pt(3 5 5) the steps are even more reactive. © 2007 Elsevier B.V. All rights reserved.